IMPLEMENTATION OF FAMILY CENTERED-CARE (FCC) THEORY IN TELEHEALTH AS E-PARENTING FOR GOLDEN AGE CHILDREN TO PREVENT STUNTING: A LITERATURE REVIEW STUDY: IMPLEMENTASI TEORI FAMILY CENTERED-CARE (FCC) PADA TELEHEALTH SEBAGAI E-PARENTING UNTUK ANAK USIA EMAS DALAM MENCEGAH STUNTING: STUDI TINJAUAN PUSTAKA - Azizah, Aufa; Wildana, Fahmi; Prastiani, Ananda Eka; Rasni, Hanny (BIMIKI (Berkala Ilmiah Mahasiswa Ilmu Keperawatan Indonesia), 2022)
Introduction: Stunting is a problem of malnutrition, recurrent infections, and inadequate psychosocial stimulation which causes disturbances in child development. Poor nutritional management in golden-age children is still a problem in many countries, including Indonesia. Management efforts are a challenge because the dissemination of information and education about stunting is not evenly distributed so awareness of nutrition management to prevent stunting is still low. This study aims to analyze and explain telehealth as e-parenting with the Family Centered-Care approach as an effective intervention in preventing stunting in the era of society 5.0. Method: The method in this study is to use a literature review. Articles are obtained through search sites such as Google Scholar, Science Direct, Scopus, NCBI, and ProQuest as well as books that are relevant to the topic. The criteria used in searching in Indonesian and English with the publication year range of 2018-2022 for journals then carried out analysis and synthesis using the PRISMA method. Results: The effectiveness of interventions provided via telehealth with a Family Centered-Care approach is oriented towards client resources at home, but remains under the supervision of health workers. This intervention significantly impacts lifestyle changes including physical activity, health education, and nutrition management. Conclusion: Telehealth can be a new alternative in the era of society 5.0 as an effort to cut time and mobilize more efficiently so that understanding and dissemination of information is wider and more equitable so that stunting can be prevented at an early age. Keywords: Family Centered-care; Nutrition Management; Parenting; Stunting; Telehealth